Power electronics: converters, applications, and design - Mohan, Ned; Undeland, Tore M; Robbins, Willim P (Delhi: Wiley India, 2015)
About the book: The text includes cohesive presentation of power electronics fundamentals for applications and design in the power range of 500 kW or less. It describes a variety of practical and emerging power electronic converters made feasible by the new generation of power semiconductor devices. Topics included in this book are an expanded discussion of diode rectifiers and thyristor converters as well as chapters on heat sinks, magnetic components which present a step-by-step design approach and a computer simulation of power electronics which introduces numerical techniques and commonly used simulation packages such as PSpice, MATLAB and EMTP.
Keywords: Electronic and Communication Engineering; Power electronic systems; Switch-mode converters; Power diodes; Thyristors; Gate and base drive circuits; Magnetic components; Synchronous motor drives